83.2k views
1 vote
How do you factor?: 4x^2 + 12x + 9 (Please show steps)

User Zymawy
by
4.7k points

1 Answer

5 votes

Answer: Rewrite 4x squared as (2x) squared

(2x) squared +12x + 9

rewrite 9 as (3) squared

Check the middle term by multiplying

2ab and compare this result with the middle term in the original expression.

2ab = 2 x (2x) x 3

Simplify 2ab = 12x, then factor using the perfect square trinomial rule. A sqaured + 2ab + b squared = (a + b) squared

A = 2x and B = 3

So your answer is

(2x + 3) squared!

sorry its so long

User Rebecka
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.